Analisis Performance Pada Layanan Internet Universitas Islam Indragiri dengan Menerapkan Metode Quality of Service - Jefitra Abdu Ar Razzak; Iwan Iskandar; Nazruddin Safaat Harahap; Reski Mai Candra (STMIK Budi Darma, 2023)
The internet network can facilitate the learning process packaged in digital content. The use of the internet as a learning medium has become commonplace among students. With the internet as a learning resource, it is easier for us to access various sources of information. Therefore, it is necessary to measure and analyze the internet network to ensure that the network used does not hinder activities that require internet access. This research aims to analyze the performance of the internet service at the Islamic University of Indragiri using the Quality of Service (QoS) method. Measurements were conducted using the Wireshark application on 7 WiFi networks with 4 types of websites as testing targets. The four main parameters are throughput, packet loss, delay, and jitter. The research results show that during peak hours, the throughput at campus 1 and campus 2 is relatively low with a value of index 2, while during off-peak hours, the throughput at both campuses is at index 4. Packet loss at campus 1 during peak and off-peak hours shows low numbers with index 4. However, at campus 2, there is an increase in packet loss during peak hours with index 4. During peak hours, the delay at campus 1 is at index 4, and the delay at campus 2 is at index 3. During off-peak hours, the delay at both campuses is at index 3 and 4. During peak and off-peak hours, the jitter at both campuses is at index 4. Based on the analysis results, it can be concluded that the WiFi network at the Islamic University of Indragiri has good performance. However, better network management is needed to maintain optimal performance during peak hours.